PENINGKATAN PENGETAHUAN KELOMPOK NELAYAN MELALUI PELATIHAN TEKNIK PEMBENIHAN KEPITING RAJUNGAN - Hakim, Irma; Nur Insana Salam; Syafiuddin (Jurnal Dedikasi Masyarakat, 2020)
Until now, small crab cultivation in fishing ponds has not been well developed in Mattiro Bombang Village. This is because the crab population along Salemo Island and Sabangko Island is decreasing, leaving the need for crab meat for export unmet. The limited availability of natural seeds among fishing groups has resulted in the small crab cultivation business, initiated last year, also experiencing a decline in production. The PPDM team cares about the problems experienced by fishermen. The next step taken by the team is to provide a training program on crab hatchery technology to the Independent Fishermen Group and the Living Together Fishermen Group. Implementation of PPDM activities uses lecture, discussion, and training methods. The developments obtained after the training show the progress of fishermen's knowledge and the very rapid increase in crab production in the last few months. However, various things still have to be implemented to obtain satisfactory results and improve the economic level of fishermen. One thing fishermen can implement is to produce their crab seeds to solve the problem of a shortage of seeds in anticipation of the development of crab enlargement which is expected to accelerate in the next decade.